2021
DOI: 10.1111/gove.12534
|View full text |Cite
|
Sign up to set email alerts
|

Taking the bite out of administrative burdens: How beneficiaries of a Mexican social program ease administrative burdens in street‐level interactions

Abstract: Despite taking the citizen experience of policy implementation as starting point for analysis, the literature on administrative burdens has mostly portrayed citizens as passive victims of burdens. Based on a literature review, three hypotheses are formulated regarding citizens' capacity to ease the impact of administrative burdens through behavioral adjustment, use of social and human capital, and strategic behavior. Evidence for these strategies is found in a case study of beneficiaries' behavior in a Mexican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Masood and Nisar (2021, p. 57) propose that administrative capital, or “explicit or tacit knowledge of bureaucratic rules, processes, and behaviors,” drives outcomes. In the most recent incarnation of this idea, Peeters and Campos (2021) argue that citizens learn from their encounters with the state, adjust their behavior, and leverage social capital to overcome burdensome processes and ultimately secure access.…”
Section: Administrative Burden Meta‐narrativesmentioning
confidence: 99%
“…Masood and Nisar (2021, p. 57) propose that administrative capital, or “explicit or tacit knowledge of bureaucratic rules, processes, and behaviors,” drives outcomes. In the most recent incarnation of this idea, Peeters and Campos (2021) argue that citizens learn from their encounters with the state, adjust their behavior, and leverage social capital to overcome burdensome processes and ultimately secure access.…”
Section: Administrative Burden Meta‐narrativesmentioning
confidence: 99%
“…Recent years have seen a massive surge in research about the detrimental impact of administrative burden on policy take-up and—more generally—program success (Bell & Smith, 2022; Christensen et al, 2020; Assouline et al, 2022). Multiple studies have shown how citizens’ experiences of learning, compliance, and psychological costs tend to increase with onerous policy design, such as time-consuming application tasks, demanding eligibility requirements, or complicated rules (Bækgaard et al, 2021; Chudnovsky & Peeters, 2021; Fox et al, 2020; Moynihan et al, 2016; Peeters & Campos, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In societies that regard welfare negatively, eligible households may experience more welfare stigma and feel less deserving than those with a more positive view of welfare (Hümbelin, 2019). Welfare policy may also affect the behaviours of street-level administrators who promote or inhibit take-up by eligible households (Berkel, 2020; Peeters and Campos, 2021). Social networks may influence the norms surrounding welfare participation and thereby affect stigma.…”
Section: Introductionmentioning
confidence: 99%